The Blackwell handbook of principles of organizational behavior - Locke, Edwin A. (Oxford, UK ; Malden, MA : Blackwell Business, 2000)
The handbook provides students and managers with an essential resources that is neither theory divorced from practice nor practice divorced from theory but rather the application of theory to the real world of organisation.
Includes bibliographical references and index.
uaj 20/02/2015
Loan
Keywords: Organizational behavior